2004
DOI: 10.4049/jimmunol.172.3.1809
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Indirectly Activates Human Neutrophils via Induction of TNF-α

Abstract: Leptin, the satiety hormone, appears to act as a link between nutritional status and immune function. It has been shown to elicit a number of immunoregulatory effects, including the promotion of T cell proliferative responses, and the induction of proinflammatory cytokines. Leptin deficiency is associated with an increased susceptibility to infection. As polymorphonuclear neutrophils (PMN) play a major role in innate immunity and host defense against infection, this study evaluated the influence of leptin on P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
155
1
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(179 citation statements)
references
References 42 publications
12
155
1
11
Order By: Relevance
“…The characteristics were consistent with the results reported by Zarkesh-Esfahani et al [23] showing that leptin has no direct effect on human PMN activation, and also those by Ottonello et al [17] demonstrating that leptin shows no secretagogue properties such as superoxide production in human PMN. However, these are rather conflicting with the reports by Caldefie-Chezet et al [4,5] who demonstrated that leptin is capable of inducing hydrogen peroxide and enhancing PMA-induced superoxide produc- Fig.…”
Section: (A) (B) (C) (D)supporting
confidence: 82%
See 2 more Smart Citations
“…The characteristics were consistent with the results reported by Zarkesh-Esfahani et al [23] showing that leptin has no direct effect on human PMN activation, and also those by Ottonello et al [17] demonstrating that leptin shows no secretagogue properties such as superoxide production in human PMN. However, these are rather conflicting with the reports by Caldefie-Chezet et al [4,5] who demonstrated that leptin is capable of inducing hydrogen peroxide and enhancing PMA-induced superoxide produc- Fig.…”
Section: (A) (B) (C) (D)supporting
confidence: 82%
“…One noticeable difference between human and bovine PMN is that human PMN express only a short isoform of leptin receptor (Ob-Ra) lacking the large part of the intracellular domain [23], whereas bovine PMN expressed a long isoform of leptin receptor (Ob-Rb). We therefore speculate, although leptin had no effect on degranulation and superoxide production, it might influence bovine PMN functions, such as chemotaxis as observed in human PMN [17].…”
Section: (A) (B) (C) (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…11 In macrophages, leptin acts as a potent chemoatractant and induces the production of inflammatory mediators including LTB 4 , TNFα and IL-6 among others. [12][13][14] Lymphocytes are also activated by leptin, which stimulates the proliferation of Th1 cells, leading to increased production of IL-1 and IFNγ. Such activation may play a role on the development of autoimmune diseases.…”
Section: Leptin Modulation Of Immune Responsesmentioning
confidence: 99%
“…Leptin is secreted 2-3 times more highly from subcutaneous than from visceral adipose tissue and correlates more strongly with adiposity in females [12,17]. Leptin promotes T-helper type 1 cell differentiation and increases activation of neutrophils via tumour necrosis factor (TNF)-a [18]. Indeed, in a mouse pneumococcal pneumonia model, exogenous leptin stimulated the innate immune response leading to increased neutrophils and IL-6 in bronchoalveolar lavage fluid [19].…”
mentioning
confidence: 99%